Analisis Strategi Branding Menggunakan Ansoff Matrik Dalam Menarik Minat Calon Mahasiswa Baru Universitas Katolik Parahyangan - Imelda, Melvi; Hendriyani, Chandra; Ruslan, Budiana (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to explore the branding strategy carried out by public relations at Parahyangan Catholic University. To attract prospective students private universities, they use various methods, including by carrying out intensive marketing strategies and promoting the identity of the university so that it is better known to the public. By using a qualitative approach through phenomenological methods, data collection was carried out by literature studies, observations and interviews. The research data analysis technique uses Ansoft Matrix analysis in a branding strategy to attract prospective new students. UNPAR provides the latest marketing product innovations with accreditation competitiveness from grade A to Superior, from Superior to International standards so that prospective students are interested in registering. Keywords: Branding Strategy, Ansoff Matrix Analysis, Interests, Marketing